Health support directed at lesbian, gay and bisexuals : sociodemographic context and education - Cunha, Madalena (2017)
Introduction: Promoting the dignity of people and equality of access to care are two fundamental pillars of good healthcare practice. Thus, producing evidence on educating and investigating competencies and practices aimed at lesbian, gay and bisexual (LGB) clients and their determinants constitute synergetic strategies which are necessary to ensure excellent health care for this particular group. Objective: To analyse the effects of the socio-demographic conditions and training in the care competence and practices carried out by health professionals for lesbian, gay and bisexual clients. Methodology: Descriptive study carried out on a sample of 119 Portuguese health professionals, the majority of whom are female with an average age of 37.90 years. Instruments:Sexual Orientation Counselor Competency Scale Citation (Bidell,2005) Correlates of Homophobia and Gay Affirmative Practice in Rural Practitioners (Crisp,2002), adapted by Pereira & Cunha (2014). Results: Health professionals with an age 31years and with specific training in psychological intervention were shown to have greater affirmative competence. 47.1% were shown to be competent professionals, 26.9% being highly competent and 26% incompetent. The health professionals with the highest competence were also the ones with the best health practices (66.7%). Conclusion: The results show the existence of a significant association between the socio-demographic variables and healthcare practices. They also show that the health professionals with the least competence also used inadequate healthcare practices for LGB clients. Training in affirmative competencies should provide for ethically guided therapeutic interventions which are culturally accessible and socially inclusive and thus ensuring the effectiveness of health systems.